Study of mechanisms of microbial-plant system functioning under soil salinity - Nazarov, A.V.; Pyankova, A.A.; Korsakova, E.S.; Shestakova, E.A.; Anan’ina, L.N. (Perm Federal Research Centre Journal, 2017)
Unique halophilic and halotolerant bacteria were found in the rhizosphere of plants growing near the salt dumps in Perm region. These bacteria can be used to create bio preparations that enhance the growth of plants under stressful conditions. The data obtained indicate the presence of not previously studied mechanism of the positive influence of rhizosphere microflora on plants under saline conditions due to the production by bacteria of an osmoprotective substance - ectoine.